OBTENÇÃO E CARACTERIZAÇÃO FÍSICO-QUÍMICA DE COMPÓSITO OBTIDO A PARTIR DE BORRACHA NATURAL E REFORÇOS PROVENIENTES DE RESÍDUOS AGROINDUSTRIAIS: AVALIAÇÃO DO COMPORTAMENTO TÉRMICO E DA TOXICIDADE FRENTE ARTEMIA SALINA - TALINA MEIRELY NERY DOS SANTOS (2024)
Natural rubber (NR) from the Hevea brasiliensis tree is essential in tire manufacturing due to its unique properties, including elasticity, wear resistance, impermeability to liquids and gases, and insulation capabilities. Traditionally, reinforcements such as carbon black and silica are added, but these cause various environmental impacts. Sustainable alternatives, such as NR/cellulose and NR/cashew nutshell liquid (CNSL) composites, maintain or improve the mechanical properties of rubber, reducing dependence on non-renewable resources. Additionally, CNSL has antioxidant properties and larvicidal potential against Aedes aegypti. In this context, the aim was to develop and characterize NR composites reinforced with cellulose extracted from sugarcane bagasse (SCB) and CNSL surfactant (sCNSL) to investigate the influence of these materials on the mechanical properties and thermal behavior of NR, with potential application in the production of membranes with mosquito larva inhibitory action against Aedes aegypti, a transmitter of diseases such as Dengue, Zika, Chikungunya, and Yellow Fever. The latex was commercially acquired from Bassan - SP, the cellulose was obtained from the purification of SCB, and the sCNSL was obtained from the saponification of CNSL. The NR and composites were obtained by the casting method. To compare the behavior in composites, commercial cellulose (CO) and cellulose obtained from SCB were used. The nomenclature adopted for the rubber and composites obtained were: 1) NR, 2) NR/CEL CO, 3) NR/CEL SCB, 4) NR/sCNSL, 5) NR/CEL CO/sCNSL, and 6) NR/CEL SCB/sCNSL. The NR and composites were characterized using Scanning Electron Microscopy (SEM), Thermogravimetry/Derivative Thermogravimetry (TG/DTG), Differential Scanning Calorimetry (DSC), Dynamic Mechanical Analysis (DMA), and Fourier Transform Infrared Spectroscopy (FTIR). Acute toxicity analysis was also performed on Artemia salina for the samples NR, NR/CEL SCB, NR/sCNSL, and NR/CEL SCB/sCNSL. The casting method proved effective, as it was possible to obtain the NR membrane and composites. TG and DSC curves were obtained in different atmospheres (nitrogen and synthetic air) with heating rates of 5, 10, 15, and 20 °C min-1. TG/DTG curves indicated distinct thermal stability for NR and composites when comparing different atmospheres, in synthetic air around 235-275 °C and in N2 around 245-290 °C. DSC curves showed that the glass transition temperatures (Tg) of NR and composites were around -60 °C, indicating that the addition of materials to the rubber did not interfere with Tg. FTIR spectra and DSC curves indicated a similar profile for both celluloses, suggesting the efficiency of the SCB CEL purification process. The FTIR spectrum of the NR/CEL SCB/sCNSL composite presented characteristic bands of the materials added to NR (3400, 3000-2840, 1600, 1440-1220, 821 cm-1). Surface micrographs of the celluloses indicated different morphologies; SCB cellulose showed elongated and irregular fibers, while commercial cellulose had short and fragmented fibers due to the sieving process. The obtained composites containing cellulose exhibited a biphasic system. DMA curves showed glass transition temperatures (Tg) around -60 °C; however, the NR membrane and NR/sCNSL composite showed unusual curve profiles and Tg temperatures at -52.6 °C, requiring further studies. Acute toxicity analysis with Artemia salina showed non-toxicity at different exposure times. Additionally, the addition of SCB CEL and sCNSL to NR contributed to an increase in LC50 compared to the unmodified sample (NR). It is concluded that the addition of materials to NR did not cause negative impacts on NR characteristics, enabling a range of applicability for the produced material.